Protein phosphatase 2A is crucial for sarcomere organization in Caenorhabditis elegans striated muscle - Qadota, Hiroshi (Mol Biol Cell, 2018)
Protein phosphatase 2A (PP2A) is a heterotrimer composed of single catalytic and scaffolding subunits and one of several possible regulatory subunits. We identified PPTR-2, a regulatory subunit of PP2A, as a binding partner for the giant muscle protein UNC-89 (obscurin) in Caenorhabditis elegans. PPTR-2 is required for sarcomere organization when its paralogue, PPTR-1, is deficient. PPTR-2 localizes to the sarcomere at dense bodies and M-lines, colocalizing with UNC-89 at M-lines. PP2A components in C. elegans include one catalytic subunit LET-92, one scaffolding subunit (PAA-1), and five regulatory subunits (SUR-6, PPTR-1, PPTR-2, RSA-1, and CASH-1). In adult muscle, loss of function in any of these subunits results in sarcomere disorganization. rsa-1 mutants show an interesting phenotype: one of the two myosin heavy chains, MHC A, localizes as closely spaced double lines rather than single lines. This “double line” phenotype is found in rare missense mutants of the head domain of MHC B myosin, such as unc-54(s74). Analysis of phosphoproteins in the unc-54(s74) mutant revealed two additional phosphoserines in the nonhelical tailpiece of MHC A. Antibodies localize PPTR-1, PAA-1, and SUR-6 to I-bands and RSA-1 to M-lines and I-bands. Therefore, PP2A localizes to sarcomeres and functions in the assembly or maintenance of sarcomeres.